2006
DOI: 10.1007/s11192-006-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced indicators of productivity of universitiesAn application of robust nonparametric methods to Italian data

Abstract: This paper explores scale, scope and trade-off effects in scientific research and education. External conditions may dramatically affect the measurement of performance. We apply theDaraio&Simar's (2005) nonparametric methodology to robustlytake into account these factors and decompose the indicators of productivity accordingly. From a preliminary investigation on the Italian system of universities, we find that economies of scale and scope are not significant factors in explaining research and education produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 36 publications
4
101
0
12
Order By: Relevance
“…Hence, it is possible to find works using this approach to measure the efficiency of units operating in multiple frameworks such as the educational sector (Bonaccorsi et al, 2006;Cherchye et al, 2010;De Witte and Rogge, 2011;Haelermans and De Witte, 2012;De Witte and Kortelainen, 2013;, banks and mutual funds (Daraio and Simar, 2005;Daouia and Simar, 2007;Blass et al, 2008;Badin et al, 2010), post offices (Cazals et al, 2008), public libraries (De Witte and Geys, 2011;, regional welfare or environment Tzeremes, 2011a, Halkos andTzeremes, 2013), local services (Rogge and De Jaeger, 2012;Verschelde and Rogge, 2012) or the water sector Marques, 2010a, 2010b;Carvalho and Marques, 2011;Vidoli, 2011). However, to the best of our best knowledge, this methodology has only been applied previously in the health sector to measure the efficiency of health administrative districts in Greece (Halkos and Tzeremes, 2011b) considering only continuous exogenous variables.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is possible to find works using this approach to measure the efficiency of units operating in multiple frameworks such as the educational sector (Bonaccorsi et al, 2006;Cherchye et al, 2010;De Witte and Rogge, 2011;Haelermans and De Witte, 2012;De Witte and Kortelainen, 2013;, banks and mutual funds (Daraio and Simar, 2005;Daouia and Simar, 2007;Blass et al, 2008;Badin et al, 2010), post offices (Cazals et al, 2008), public libraries (De Witte and Geys, 2011;, regional welfare or environment Tzeremes, 2011a, Halkos andTzeremes, 2013), local services (Rogge and De Jaeger, 2012;Verschelde and Rogge, 2012) or the water sector Marques, 2010a, 2010b;Carvalho and Marques, 2011;Vidoli, 2011). However, to the best of our best knowledge, this methodology has only been applied previously in the health sector to measure the efficiency of health administrative districts in Greece (Halkos and Tzeremes, 2011b) considering only continuous exogenous variables.…”
Section: Introductionmentioning
confidence: 99%
“…An open issue is the choice of parameter m. The literature does not yet provide a definite rule on how to choose the value of m. "Experience has shown that in many applications, qualitative conclusions are little affected by particular choices of m, provided the values of m are somewhat less than the sample size, n" (Simar and Wilson, 2006, p. 78). Here we follow Bonaccorsi et al (2005) in setting the level of robustness to ten percent, i.e. ten percent of the units are outside the frontier.…”
Section: A Methods To Calculate Innovation Performancementioning
confidence: 99%
“…They are located in between a homogenous institutionalized setting and heterogeneous accumulation of faculties. The university level appears to be the only level that provides the possibility of examining the interplay and relation of the three missions -to which we will come back later -as they are consistent among countries (Bonaccorsi, Daraio, & Simar, 2006). Considering strategic orientation and institutional as well as regional factors that are affecting universities is nowadays essential with regards to the positioning in the higher education context, an advantageous allocation of scarce resources and the development of group-specific strategies (Warning, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%